Development of a self-guided web-based exercise intervention (SPIN) to treat shoulder pain in people living with spinal cord injury: protocol of a mixed methods study - Nicola Saywell; Verna Stavric; Nicola Maree Kayes (BMJ Open)
Introduction Chronic shoulder pain is common after spinal cord injury (SCI) and limits community mobility. This leads to loss of independence and reduced quality of life. Evidence suggests that exercises can help reduce shoulder pain. However, cost, expertise and transport barriers frequently limit access to treatment services. The objective of this study is to develop an evidence-based, acceptable, usable and persuasive self-guided web-based exercise intervention to treat shoulder pain in people living with SCI.Methods and analysis An iterative and phased person-based approach (PBA) will capture users’ perspectives on usability and acceptability to develop guiding principles that will shape the design of the intervention. The intervention will be based on key elements identified through participant input and from evidence identified through systematic and narrative reviews, to ensure the intervention addresses participants’ needs and increase the likelihood of uptake. The prototype will be iteratively refined through focus groups and think-aloud sessions. Review data will be synthesised drawing on systematic and narrative review conventions. Qualitative data will be analysed using conventional content analysis (planning phase) and directed content analysis (development phase) to inform intervention design and refinement.Ethics and dissemination Ethical approval has been granted by the Auckland University of Technology Ethics Committee (AUTEC) in Auckland, New Zealand. The results of the study will be published in a peer-reviewed journal and presented at relevant national and international conferences. A summary of findings will be presented to key stakeholder groups. We will progress to a definitive trial should the findings from this intervention development study indicate the intervention is acceptable and usable.